Evaluasi Penerapan Akuntansi Persediaan Pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Kepulauan Talaud - Elisya Pulu (Jurnal LPPM Bidang EkoSosBudKum (Ekonomi,Sosial,Budaya, dan Hukum), 2022)
This study aims to determine the suitability of the application of inventory accounting with applicable standard, which are set at the Agency for Personel and Human Resource Development, Talaud Islands Regency. Inventory accounting is one of the important elements in realizing good financial reports. 1. Inventory classification, 2. Inventory recognition, 3. Inventory measurement, 4. Inventory expense, 5. Inventory recording system and 6. Inventory disclosure. The applicable standard reffered to in this research is Accrual-Based Inventory Accounting Standard Statement Number 5 concerning Inventory Accounting which contained in Government Regulation Number 71 of 2010. In analyzing the data is by using qualitative descriptive analysis techniques. The results of this study indicate that the inventory accounting in the Agency for Personel and Human Resources Development In the Talaud Island Regency is in accordance with applicable standards.